ACE I/D polymorphism associated with muscle strength and its relation to the health status of people over 60 years of age - Marciniak, Anna; Kłoska, Sylwester; Woźniak, Marcin; Perkowski, Radosław; Podhorecka, Marta; Gębka, Dominika; Androsiuk-Perkowska, Joanna; Kozłowski, Henryk; Kędziora-Kornatowska, Kornelia; Zukow, Walery (Journal of Education, Health and Sport, 2018)
Among older people, a big problem is the decrease in both muscle strength and general physical fitness. This often prevents the proper functioning of a person, which makes him or her dependent on their guardians or family. It is believed that the ACE gene is associated with better results achieved in strength sports. It may also be related to the health condition of older people. For this purpose, a study was conducted on a group of 60 people over 60 years of age. The study was conducted with the consent of the bioethical commission and under the supervision of physiotherapists. The relationship between overall fitness and muscle strength of older people with ACE genotypic variants was checked. For this purpose, a questionnaire on physical activity of IPAQ was used. On its basis, the values ​​of MET and BMI coefficients were determined. Fitness tests were also carried out, i.e. SPPB, DGI and Up & Go. The ACE gene was tested by PCR. The insertion-deletion polymorphism of the Alu sequence in this gene was examined. It was found that: DD gene genotype ACE is associated with higher values ​​of BMI and shorter standing time on the left leg (p<0.05), genotype II is associated with lower overall physical activity determined on the basis of MET (p<0.05), genotype ID is associated with better results in the left leg test (p<0.05). Based on obtained results it is impossible to determine if ACE gene has clear impact on muscle strength and health of the older adults.